1997
DOI: 10.1017/s1431927697970264
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Grain Boundary Relaxation Modes in Metals and Ceramics

Abstract: The atomic-scale structure of tilt grain boundaries has been studied by high-resolution electron microscopy (HREM) in several ceramics and metals such as NiO, yttria stabilized zirconia, Au, and Al. It is found that when grain boundaries are formed between two crystals a considerable variety of modes of relaxations, i.e., the rearrangements of atoms in and near the grain boundary core are possible, depending on grain boundary geometry and the interatomic interactions. The atomic relaxations within and near the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 32 publications
(45 reference statements)
3
8
0
Order By: Relevance
“…From the calculation results given in Fig. 9 it is clear that the GB energy is a nearly linear function of the excessive volume, which qualitatively agrees with the data reported by other workers [33]. The calculated proportionality factor is equal to 1600 (mJ/m 2 )/Å, with the uncertainty being 12%.…”
Section: Characteristic Features Of Grain-boundary Diffusion In Ufg-msupporting
confidence: 89%
See 1 more Smart Citation
“…From the calculation results given in Fig. 9 it is clear that the GB energy is a nearly linear function of the excessive volume, which qualitatively agrees with the data reported by other workers [33]. The calculated proportionality factor is equal to 1600 (mJ/m 2 )/Å, with the uncertainty being 12%.…”
Section: Characteristic Features Of Grain-boundary Diffusion In Ufg-msupporting
confidence: 89%
“…There is a well-known example of such behavior of the GB energy, i.e., the excessive free energy of a crystal associated with GBs and calculated per unit area of GB. As a result of numerous theoretical investigations of GBs in fcc-and bcc-metals it was shown that the energy of GBs is a nearly linear function of the excessive volume [33]. Building such relationships allows one to interpolate the simulation results for the case of SMC and NC materials using the experimentally obtained excessive volumes δV in these materials.…”
Section: Characteristic Features Of Grain-boundary Diffusion In Ufg-mmentioning
confidence: 99%
“…This is quite surprising and atypical for high-angle grain boundaries in oxides. In metals a similar behavior is found for the connection between (111) planes across the asymmetric (557)(113), [110] tilt GB in Au [3]. In this case the GB dissociates by the incorporation of periodically spaced short lengths of stacking faults.…”
Section: Methodssupporting
confidence: 52%
“…Previous experimental and simulation investigations in several fcc metals indicated that generation of twins or stacking faults from GBs, both evolving emission of partial dislocations, may induce GB dissociation (27,28). It provides a general approach to GB relaxation for lowering the energy state, especially in those metals with low stacking fault energy such as Cu.…”
Section: Resultsmentioning
confidence: 99%